Dihydroporphyrin iron (III) enhances low temperature tolerance by increasing carbon and nitrogen metabolism in Andrographis paniculata - Jian, Shao-Fen; Huang, Yan-Fen; Chen, Dong-Liang; Zhong, Chu (Frontiers in Plant Science, 2025)
Dihydroporphyrin iron (DH-Fe) is a novel plant growth regulator that plays significant roles in plant stress resistance. We found that Andrographis paniculata is extremely sensitive to low temperature (LT) with a threshold of 25°C. To evaluate whether and how DH-Fe alleviates LT stress in A. paniculata, different DH-Fe concentrations (0, 10, 20, and 40 μg·L-1) were applied to estimate its effects on C and N metabolism and antioxidative capacity in A. paniculata grown under 20°C. Pre-treatment of DH-Fe alleviated LT-induced anthocyanin accumulation. Additionally, it relieved LT-induced oxidative stress by increasing the activity of catalase (CAT). DH-Fe reduced the contents of sucrose, soluble sugar and starch and the activities of sucrose synthase (SS) and hexokinase (HXK), but stimulated the activities of sucrose phosphate synthase (SPS), glucose-6-phosphate dehydrogenase (G6PDH), glyceraldehyde 3-phosphate dehydrogenase (GAPDH), phosphoenolpyruvate carboxylase (PEPC), isocitrate dehydrogenase (ICDH), and malic enzyme (ME). Soluble protein and proline contents were decreased by DH-Fe, while total N and free amino acids contents were increased, accompanying by the enhancement of the activities of glutamine synthase (GS), glutamic-oxaloacetic transaminase (GOT) and glutamic-pyruvic transaminase (GTP). Simultaneously, the content of andrographolide, the bioactive ingredient of A. paniculata, was remarkably declined. These results indicated that DH-Fe alleviates LT-induced oxidation by increasing sugar catabolism and allocating C metabolic flow to N assimilation. A concentration of 20 μg·L-1 DH-Fe is recommended to be used to enhance LT tolerance in A. paniculata. Our results update the understanding of the mechanism of plant cold tolerance and provide new ideas for relieving plant cold damage.